Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability